Effects of magnetic field on 3D double diffusive convection in a cubic cavity filled with a binary mixture - Maatki, Chemseddine; Kolsi, Lioua; Öztop, Hakan Fehmi; Chamkha, Ali; Borjini, M. Naceur; Ben Aissia, Habib; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2013)
This paper presents a numerical study of a double diffusive convection in a cubic cavity filled with a binary mixture. The vertical walls are given different temperatures and concentrations. The potential-vorticity formulation in three-dimensional configuration using the finite volume method is utilized in this study. The results are given for Rayleigh number Ra = 10(5), Pranda number Pr = 10 and Lewis number Le = 10, characterizing the case of aqueous solutions. The influence of the magnetic field on the structure of the three-dimensional flow, the distribution of temperature and concentration and the different characteristics of heat and mass transfer of the thermal and solutal dominated region are presented. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Double diffusive convection; Magnetic field; 3D cubic cavities; Spiral flow